Operational Modal Analysis of a Box Girder Bridge using Fast Fourier Transform and Stochastic Subspace Identification - Akbar, Muhammad; Aminullah, Akhmad; Awaludin, Ali (Universitas Negeri Yogyakarta, 2025)
The A.P. Pettarani Flyover Bridge in Makassar serves as a critical infrastructure supporting community mobility and regional economic activities. With the increasing volume of traffic and the resulting structural loads, the implementation of a Structural Health Monitoring System (SHMS) becomes essential to ensure both the safety and maintenance efficiency of the bridge. This study aims to explore the application of Operational Modal Analysis (OMA) through the use of Fast Fourier Transform (FFT) and Stochastic Subspace Identification (SSI) methods to analyze the bridge's structural health by extracting natural frequencies and damping ratios from dynamic response data. Dynamic response data were obtained through permanently installed accelerometers, enabling continuous monitoring of the bridge’s vibrational behavior due to traffic loads and environmental influences. The FFT analysis effectively identified the dominant frequency at 3.92 Hz, consistent with the results from SSI analyses both SSI Data and SSI Covariance methods which also yielded a natural frequency of 3.92 Hz. Additionally, other frequencies were observed in the range of 9.80 Hz to 9.81 Hz, with corresponding damping ratios varying between 1% and 3%. The consistency in natural frequency results from both methods highlights the reliability of OMA in capturing the modal characteristics crucial for structural health assessment. Harnessing modern sensor technology and advanced spectral and subspace identification techniques, this monitoring system facilitates early detection of potential damage before it evolves into more significant issues. The practical implications of this research include enhancing maintenance strategies toward more targeted and sustainable bridge management. Furthermore, the success of this study provides a valuable reference model for the continual development of SHMS for other bridges throughout Indonesia, ultimately promoting road user safety and the longevity of national infrastructure.